Shakespeare in the Theatre: Sir William Davenant and the Duke's Company - Winkler, Amanda Eubanks (Shakespeare in the Theatre, 2021)
Eubanks Winkler and Schoch reveal how - and why - the first generation to stage Shakespeare after Shakespeare's lifetime changed absolutely everything. Founder of the Duke's Company, Sir William Davenant influenced how Shakespeare was performed in a profound and lasting way. This open access book provides the first performance-based account of Restoration Shakespeare, exploring the precursors to Davenant's approach to Restoration Shakespeare, the cultural context of Restoration theatre, the theatre spaces in which the Duke's Company performed, Davenant's adaptations of Shakespeare's plays, acting styles, and the lasting legacy of Davenant's approach to staging Shakespeare. The eBook editions of this work are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Queens University Belfast.